The Fine Line between Nudging and Nagging: Increasing Take-up Rates through Social Media Platforms - Maria José Urbina; Andres Moya; Sandra V. Rozo (Institute of Labor Economics (IZA), 2023)
This study assesses if nudges in the form of informational videos sent via WhatsApp are effective in boosting take-up rates among vulnerable populations, specifically in the context of a regularization program for Venezuelan forced migrants in Colombia. The study randomly assigned 1,375 eligible migrants to receive one of three informational videos or be in a control group. The videos aimed at solving issues related to awareness, trust, and bottlenecks in the step-by-step registration. The main results indicate that program take-up rates for individuals who received any video, were eight percentage points lower compared to the control group. The effects are mostly driven by the treated individuals who received the links but did not watch the videos, who are older, busier, and with less internet access relative to other treated individuals. Additionally, the study evaluates the effectiveness of iterative WhatsApp surveys in collecting data from hard-to-reach populations. It finds that iterative WhatsApp surveys had low retention rates, and iterative contacts do not helped to reduce attrition.
Keywords: D72; F02; F22; O15; R23; 330; refugees; amnesties; program take-up